2020
DOI: 10.1002/solr.202000551
|View full text |Cite
|
Sign up to set email alerts
|

High Open‐Circuit Voltage in Full‐Inorganic Sb2S3 Solar Cell via Modified Zn‐Doped TiO2 Electron Transport Layer

Abstract: Antimony sulfide (Sb2S3) is emerging as a popular photovoltaic candidate for thin‐film solar cells due to its large absorption coefficient, suitable bandgap, nontoxic, and earth‐abundant nature. The performance of thermally evaporated Sb2S3 devices is severely restricted by interfacial recombination leading to high open‐circuit voltage (VOC) losses. CdS as electron transport layer (ETL) has overcome this problem, but triggered lower JSC issues due to parasitic absorption loss conceding to its smaller bandgap. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…have been used to address these disadvantages. [80,82] For example, Niobium (Nb) is doped into TiO 2 to modify the photo-electrical properties of TiO 2 film. [80] Composition engineering…”
Section: Tiomentioning
confidence: 99%
See 1 more Smart Citation
“…have been used to address these disadvantages. [80,82] For example, Niobium (Nb) is doped into TiO 2 to modify the photo-electrical properties of TiO 2 film. [80] Composition engineering…”
Section: Tiomentioning
confidence: 99%
“…[81] More recently, Ishaq et al used Zn doped TiO 2 as ETL in planar-type Sb 2 S 3 solar cells. [82] They found that Zn-doped TiO 2 enhanced the interface quality and induced a upward shift of the Fermi level from 4.25 to 4.19 eV, which leads to the improvement of charge extraction and transportation as well as the suppression of charge recombination losses.…”
Section: Tiomentioning
confidence: 99%
“…Finally, the device based on TiO 2 ETL modified via ZnCl 2 delivered the optimal PCE of 7.08%. While, apart from Sb 2 S 3 surface modifications by an inorganic salt zinc halide, Ishaq et al [114] in a collaboration with our group, introduced a Zn doping strategy in the TiO 2 ETL, by adding different concentrations of ZnCl 2 powder to the TiO 2 solution. In the end, the PCE of the device based on pure-TiO 2 was 4.41%, and due to the excellent junction quality with Zn-TiO 2 , the PCE of the device reached 5.16%, with a V OC of 702 mV for Cd-free full-inorganic Sb 2 S 3 solar cell.…”
Section: Electron Transport Layersmentioning
confidence: 99%
“…Reproduced with permission. [114] Copyright 2020, Wiley-VCH. d) Schematic diagram of selenization of Sb 2 S 3 photovoltaic device in two-zone tube furnace.…”
Section: Defects Passivation Strategiesmentioning
confidence: 99%
“…Recently, Ishaq et al [ 39 ] reported a Sb 2 S 3 planar solar cell using Zn‐doped TiO 2 compact layers obtained by spray pyrolysis and Sb 2 S 3 films obtained by a rapid thermal evaporation process. They found that by controlling the Zn concentration in the spray pyrolysis solution, the morphology, crystallinity, and energy bands of TiO 2 can be effectively tuned.…”
Section: Resultsmentioning
confidence: 99%